KONSEP YAHUDI DALAM AL-QUR’AN: (Aplikasi Teori Kontekstual Abdullah Saeed) - Rahman, Nailur (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
This paper highliths the study of Jewish concepts in the Koran by applying contextual interpretation theory of Abdullah Saeed. Broadly speaking this theory is not only focused on linguistic studies (textualism), but also focuses on the study of the social context and history of the Koran (contextualism) in order to give meaning intact towards the Qur'an in order to make relevant to the needs and circumstances of Muslims. Furthermore, the purpose of this study is also to answer the ambiguity in understanding Jewish concepts in the Koran including the understanding contained in the Qur'an which in this case its meaning becomes an important matter to be studied more deeply before obtaining a universal conclusion from the meanings of the verses has a diversity of meanings. Thus, the characteristics of the Koran as a book that can be received from previous generations to date "Salih li kulli zaman wa makan 'is always fulfilled.